First Record of Scytinopogon Angulisporus (Pat.) Corner From Bangladesh - Ahmed, Fakhruddin Ali; Hossain, Gazi Mosharof (Bangladesh Journal of Plant Taxonomy, 2021)
Abstract not available Bangladesh J. Plant Taxon. 28(2): 459-463, 2021 (December)